Vitamin D: Metabolism, Molecular Mechanisms, and Mutations to Malignancies - Nemazannikova, N.; Antonas, K.; Dass, Crispin (John Wiley & Sons, Inc., 2014)
The potential protective effects of vitamin D against cutaneous carcinogenesis are still poorly understood. The inhibition, by vitamin D, of various cancers in in vitro and in vivo models has triggered detailed investigation of vitamin D effects on neoplastic behavior. Recent studies highlight that such neoplastic features as the tumor microenvironment, angiogenesis, DNA mutagenesis, and apoptosis are all connected to vitamin D metabolic pathways. This review discusses these connections. Vitamin D modulation of the cell cycle, DNA repair and apoptosis via its receptors (VDRs) may have a suppressive effect on skin cancer as some studies suggest. The regulation of multiple tumor signaling pathways by vitamin D may have an implication in cutaneous carcinogenesis and tumor progression to malignancy.